The m6A modification of LINC01133 suppresses ER+ breast cancer progression by modulating IGF2BP2 protein stability via a ubiquitination-dependent mechanism - Li, Mai-dong; Shan, Ben-jie; Wang, Lei; Gao, Shuang; Hao, Li; Yu, Hai-yang; Pan, Yue-yin (Frontiers in Oncology, 2025)
BackgroundBreast cancer is characterized as highly heterogenous and is a representative model to understand how molecular features of tumor biology determine therapeutic strategy. LINC01133 exhibits opposing expressing patterns across different breast cancer subtypes, yet its roles and mechanisms in ER+ breast cancer remain a loaded question.MethodsThe expression of LINC01133 was initially assessed utilizing a public dataset TCGA and subsequently validated within clinical samples through RT-qPCR and in situ hybridization (ISH). To determine the role of LINC01133, various assays, including colony formation, Transwell, 5-ethynyl-2′-deoxyuridine (EdU) labeling, and mouse xenograft experiments, were performed. Additionally, RNA immunoprecipitation (RIP), RNA pull-down, mass spectrometry (MS), and RNA stability assays were conducted to elucidate its mechanisms.ResultsLINC01133 was dramatically downregulated in ER+ breast cancer, which results in unfavorable prognosis. Functionally, LINC01133 inhibited migration and invasion in vitro and metastasis in vivo of ER+ breast cancer cells. Mechanistically, LINC01133 can directly interact with IGF2BP2 protein promoting its ubiquitination and degradation. The downregulation of LINC01133 was mediated by m6A modification, catalyzed by METTL3 and recognized by YTHDF2, causing half-life reduction and accelerated degradation of LINC01133.ConclusionOur findings revealed the downregulation of LINC01133 in ER+ breast cancer and provided novel insight to the role of METTL3/YTHDF2/LINC01133/IGF2BP2 axis in ER+ breast cancer, which might offer a novel perspective in the design and development of novel anticancer drugs.